Довірча власність як спосіб забезпечення виконання зобов’язань: оцінювання ризиків - Некіт, Катерина Георгіївна; Некіт, К. Г.; Nekit, Kateryna H. (Херсон : Видавничий дім «Гельветика», 2019)
Статтю присвячено оцінюванню нововведень у ЦК України, що стосуються запровадження права довірчої власності як способу забезпечення виконання зобов’язань. Досліджено досвід зарубіжних країн щодо використання довірчої власності як способу забезпечення виконання зобов’язань. Визначено ризики, які очікують практиків під час застосування довірчої власності як способу забезпечення виконання зобов’язань, у зв’язку з недоліками законодавства.

The article is devoted to the assessment of innovations in the Civil Code of Ukraine, concerning the introduction of the fiduciary ownership as a way to ensure the fulfillment of obligations. The Law of Ukraine “On Amending Certain Legislative Acts of Ukraine Concerning the Promotion of Investment Activities in Ukraine” dated September 20, 2019 is analyzed in detail. It is noted that it would be more expedient to fix a separate chapter in the Civil Code of Ukraine on fiduciary ownership (fiducia). This approach is used in all European countries where fiduciary ownership exists. Insertion in the law of fiduciary ownership simply as a way to ensure fulfillment of obligations does not provide a holistic understanding of the essence of this legal institution. In addition, this approach added even more uncertainty in understanding of legal nature of the fiduciary ownership. In particular, the fiduciary ownership is interpreted ambiguously by the legislator. It is considered simultaneously as a kind of ownership, and as a limited property right, derived from the ownership. This situation is obviously illogical and can lead to problems in the practice of using this institution. The article also assesses the risks for debtors who transfer their property in fiduciary ownership. In such a situation, debtors find themselves in an extremely disadvantaged position. Firstly, the delay periods at which foreclosure on the object of fiduciary ownership is allowed are very short. Secondly, the proposed innovations actually nullify the previously established moratorium on the inadmissibility of eviction from housing, if such property is the place of permanent residence of the debtor. Thirdly, requirements to participants in fiduciary relations are not clearly defined. There is no clear answer whether the trustee can simultaneously act as a beneficiary under the contract. It is also not clear what requirements are imposed on the fiduciary owner. For example, in European countries, the circle of trustees is limited to banks, financial institutions, insurance companies, barristers and notaries. There are no such restrictions in Ukraine. The only thing required from a trustee is to be an entrepreneur. The article also explores the experience of foreign countries in the use of fiduciary ownership as a way to ensure the fulfillment of obligations. Some positive aspects that the Ukrainian legislator can borrow were identified.
Некіт К. Г. Довірча власність як спосіб забезпечення виконання зобов’язань: оцінювання ризиків / Некіт К. Г. // Часопис цивілістики : наук.-практ. журн. / редкол.: С. В. Ківалов (голов. ред.), Є. О. Харитонов (заст. голов. ред.), К. Г. Некіт (відп. секр.) [та ін.]. - Херсон : Видавничий дім «Гельветика», 2019. – Вип. 35. – С. 28-34.
Keywords: довірча власність; фідуція; забезпечення виконання зобов’язань; право власності; речові права; fiduciary property; fiducia, ensuring obligations fulfillment; ownership; real rights; Research Subject Categories::LAW/JURISPRUDENCE